2020
DOI: 10.1093/bioinformatics/btaa531
|View full text |Cite
|
Sign up to set email alerts
|

SAINT: self-attention augmented inception-inside-inception network improves protein secondary structure prediction

Abstract: Motivation Protein structures provide basic insight into how they can interact with other proteins, their functions and biological roles in an organism. Experimental methods (e.g., X-ray crystallography, nuclear magnetic resonance spectroscopy) for predicting the secondary structure (SS) of proteins are very expensive and time consuming. Therefore, developing efficient computational approaches for predicting the secondary structure of protein is of utmost importance. Advances in developing hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 74 publications
(88 reference statements)
0
73
0
Order By: Relevance
“…We investigated the interpretability of EGRET to provide insights on how the architecture is making decisions. Some recent studies demonstrated partial interpretability of deep neural networks for solving various problems in computational biology (in particular, see Uddin et al (2020) and Vig et al (2020)).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the interpretability of EGRET to provide insights on how the architecture is making decisions. Some recent studies demonstrated partial interpretability of deep neural networks for solving various problems in computational biology (in particular, see Uddin et al (2020) and Vig et al (2020)).…”
Section: Resultsmentioning
confidence: 99%
“…In this research, we use 5 independent test sets to evaluate the performance of different approaches. CASP-FM (56), collected by SAINT 29 , contains 10 template-free modeling (FM) targets from CASP13, 22 FM targets from CASP12, 16 FM targets from CASP11, and 8 FM targets from CASP10. CASP13 (26) contains 26 FM targets from CASP13.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, π-helix is found abundant and associated with activities in some special proteins (Cooley et al, 2010 ). As a result, over the few years many efforts have been made, trying to solve the Q8 prediction problem, which is much more complicated and challenging (Li and Yu, 2016 ; Wang et al, 2016 ; Fang et al, 2017 ; Heffernan et al, 2017 ; Zhang et al, 2018 ; Krieger and Kececioglu, 2020 ; Uddin et al, 2020 ; Guo et al, 2021 ) If not otherwise specified, the models discussed in this paper are non-template based. The Q8 prediction accuracy has reached 70% and at present the best record is 77.73% (Uddin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, a variety of state-of-the-art methods have been developed to improve Q3 or Q8 prediction accuracy and most progresses are contributed by machine learning based models (Li and Yu, 2016 ; Wang et al, 2016 ; Fang et al, 2017 ; Heffernan et al, 2017 ; Zhang et al, 2018 ; Krieger and Kececioglu, 2020 ; Uddin et al, 2020 ; Guo et al, 2021 ) So far as we know, the predictive power of a machine learning model is governed mainly by two elements, namely feature representation and algorithm. For instance, the introduction of sequence evolutionary profiles from multiple-sequence alignment (Rost and Sander, 1993 ), such as position-specific scoring matrices (PSSM) (Jones, 1999 ), improves prediction accuracy significantly (Zhou and Troyanskaya, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation